2010
DOI: 10.1111/j.1600-0838.2009.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between three potentiation effects of plyometric training and performance

Abstract: Plyometric training specifically potentiated the normalized EMG, tendon stiffness and elastic energy utilization in the myotendinous complex of the triceps surae. Although these changes are possibly essential determinants, only increases of tendon stiffness were observed to correlate with performance improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 26 publications
4
92
1
6
Order By: Relevance
“…11,13 Tendon mechanical properties determine stress and strain distribution within the tendon. 37,38,40 Tendon microcirculation reflects intratendinous metabolic demands and includes the distribution of blood flow and oxygen consumption in the arteriolar, capillary, and venular segments. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11,13 Tendon mechanical properties determine stress and strain distribution within the tendon. 37,38,40 Tendon microcirculation reflects intratendinous metabolic demands and includes the distribution of blood flow and oxygen consumption in the arteriolar, capillary, and venular segments. …”
mentioning
confidence: 99%
“…11,13 Tendon mechanical properties determine stress and strain distribution within the tendon. 37,38,40 Tendon microcirculation reflects intratendinous metabolic demands and includes the distribution of blood flow and oxygen consumption in the arteriolar, capillary, and venular segments. 22,31 Local blood flow is controlled by autoregulation (myogenic responses and metabolism) and shearing stress stimulation of the endothelium and neurohormones, 31 and is partially influenced by vessel radius and length (Poiseuille's equation).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm previous suggestions that children's immature tendons adapt to training stimuli in a similar way as adults (1, 4, 12). For instance, previous studies in adults (1,12)) have shown that AT stiffness increased after 6 and 8 weeks of plyometric training, respectively. Similarly, in pre-pubertal children, Wauge et al (5) reported that 10-weeks resistance training resulted in a significant increase of AT stiffness although no change in tendon CSA has been reported (4).…”
Section: Strainmentioning
confidence: 97%
“…Achilles tendon mechanical properties adapt to chronic increases (1) or decreases (2) in mechanical loading. Few data exist on the effects of physical training on Achilles-Tendon mechanical properties on children (3,4).…”
Section: Introductionmentioning
confidence: 99%